Severe mental illness and the perimenopause - Sophie Behrman; Clair Crockett (BJPsych Bulletin)
Hormonal fluctuations in the perimenopause are associated with an array of physical and psychological symptoms. Those with pre-existing mental disorders may experience changes to their symptoms and response to treatment during the perimenopausal and postmenopausal periods and may also be at risk of poorer longer-term physical health outcomes in menopause. The transition towards menopause may be compounded by the oestradiol-suppressing effect of many psychotropics on the hypothalamopituitary–gonadal axis. A collaborative approach between primary care and secondary mental health services is an opportunity for proactive discussion of symptoms and support with management of the perimenopause. This may involve lifestyle measures and/or hormone replacement therapy, which can both lead to improvements in well-being and mental and physical health.